Costs of long-term carrying of extra mass in a songbird. (17th February 2016) - Atema, Els; van Noordwijk, Arie J.; Boonekamp, Jelle J.; Verhulst, Simon
Lay Summary: Animals face a trade-off between reproduction and survival, but how and when costs of increased workload are paid is unclear. When letting male great tits carry a small weight for 1-year, short-term costs are paid via decreased nestling weight and diminished individual state. We did not find long-term effects of hard work on fitness. This has important implications for welfare aspects of equipping birds with small devices such as transmitters. Abstract: Iteroparous organisms face a trade-off between reproduction and survival, but knowledge of whether how and when costs of long-term increases in workload are paid is scant. We increased locomotion costs for a whole year by equipping male great tits with a backpack during breeding, removing the backpacks 1 year later. We applied 3 different treatments: control (without backpack), light ("empty" backpack, 0.1g), and heavy ("full" backpack, 0.9g, ~5% of body mass). Backpacks were administered in 3 cohorts, and we monitored effects on mass of nestlings and the male, wing length, reproduction, and survival. Added mass had a negative effect on nestling mass in both the starting year of the experiment and 1 year later, but not on production of fledglings or recruits. In winter and the next breeding season, males equipped with heavy backpacks had a higher (net) body mass and had shorter third primary feathers than the other 2 groups. Heavy backpack males were less likely to sleep in a nest box in winter. Nest boxes are optimal roosting sites, and we interpret this finding as a treatment effect on success in competition over this resource. However, there was no effect of the manipulation on survival. Overall, we found no long-term fitness consequences, and we discuss possible explanations and implications for the "starvation–predation theory" of optimal body mass. However, we found short-term effects of carrying extra weight suggesting that behavioral studies using small devices should consider the effects of equipping small non-migratory passerines with devices such as transmitters.